Integrated Metabolome and Transcriptome Analyses Reveal the Mechanisms Regulating Flavonoid Biosynthesis in Blueberry Leaves under Salt Stress - Bin Ma; Yan Song; Xinghua Feng; Pu Guo; Lianxia Zhou; Sijin Jia; Qingxun Guo; Chunyu Zhang (Horticulturae)
The flavonoids play important roles in plant salt tolerance. Blueberries (Vaccinium spp.) are extremely sensitive to soil salt increases. Therefore, improving the salt resistance of blueberries by increasing the flavonoid content is crucial for the development of the blueberry industry. To explore the underlying molecular mechanism, we performed an integrated analysis of the metabolome and transcriptome of blueberry leaves under salt stress. We identified 525 differentially accumulated metabolites (DAMs) under salt stress vs. control treatment, primarily including members of the flavonoid class. We also identified 20,920 differentially expressed genes (DEGs) based on transcriptome data; of these, 568 differentially expressed transcription factors (TFs) were annotated, and bHLH123, OsHSP20, and HSP20 TFs might be responsible for blueberry leaf salt tolerance. DEGs involved in the flavonoid biosynthesis pathway were significantly enriched at almost all stages of salt stress. Salt treatment upregulated the expression of most flavonoid biosynthetic pathway genes and promoted the accumulation of flavonols, flavonol glycosides, flavans, proanthocyanidins, and anthocyanins. Correlation analysis suggested that 4-coumarate CoA ligases (4CL5 and 4CL1) play important roles in the accumulation of flavonols (quercetin and pinoquercetin) and flavan-3-ol (epicatechin and prodelphinidin C2) under salt stress, respectively. The flavonoid 3′5′-hydroxylases (F3′5′H) regulate anthocyanin (cyanidin 3-O-beta-D-sambubioside and delphinidin-3-O-glucoside chloride) biosynthesis, and leucoanthocyanidin reductases (LAR) are crucial for the biosynthesis of epicatechin and prodelphinidin C2 during salt stress. Taken together, it is one of the future breeding goals to cultivate salt-resistant blueberry varieties by increasing the expression of flavonoid biosynthetic genes, especially 4CL, F3′5′H, and LAR genes, to promote flavonoid content in blueberry leaves.